Correlation of body mass index with dynamic balance using Y-Balance Test in adults with the Flexible Flat Foot: An Analytical Correlation Research Protocol - Shobha M. Bhave; Waqar M. Naqvi; Arti I. Sahu; Sakshi P. Arora (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Balance is one of the primary requirements for both static and dynamic activities. Body MassIndex (BMI) is measurement for estimating excess body fat. The Lower Quarter Y-Balance Test (YBTLQ) is a screening instrument that measures single-leg balance in different directions. Flexible flatfoot isthe postural aspect with depressed medial longitudinal arch, pronated subtalar joint and valgus position ofcalcaneus, evident only in weight-bearing position.Methods: An analytical correlation study with 255 participants (Purposive sampling) will be taken as perinclusion and exclusion criteria with study duration of 3 years. The BMI, sit to stand Navicular Drop Test(SSNDT), limb length and medial longitudinal arch angle (MLAA) will be measured and compared. Themean score of the Y Balance Test in different categories of BMI will be compared by performing one wayANOVA test. The mean score of the Y Balance Test between two groups in each category of BMI will becompared by Bonferroni t-test.Conclusion: The study aims the correlation of BMI with the dynamic balance on Y-balanced test in adultswith flexible flat foot. The expected outcome of study will concentrate on the significant correlation of YBalance Test in different categories of BMI.